2019
DOI: 10.4314/jae.v21i3.8
|View full text |Cite
|
Sign up to set email alerts
|

Training needs of rural women entrepreneurs in non-farm enterprises in Imo State, Nigeria

Abstract: The study measured

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Rural women in Imo State have very little opportunity to access credit, which is important for them in order to expand their vegetable production or earn more income to purchase other households food. Special credit facilities for women are limited, and some of the major impediments to women's access to credit are poor infrastructure, female illiteracy, the lack of education and information, tradition and custom, and the absence of collateral, especially in the form of landownership (Obinna and Maduka, 2017).…”
Section: Type and Level Of Constraints Women Face In Vegetable Farmingmentioning
confidence: 99%
“…Rural women in Imo State have very little opportunity to access credit, which is important for them in order to expand their vegetable production or earn more income to purchase other households food. Special credit facilities for women are limited, and some of the major impediments to women's access to credit are poor infrastructure, female illiteracy, the lack of education and information, tradition and custom, and the absence of collateral, especially in the form of landownership (Obinna and Maduka, 2017).…”
Section: Type and Level Of Constraints Women Face In Vegetable Farmingmentioning
confidence: 99%
“…Furthermore, governments should emphasize on capacity-building programmes for rural women in entrepreneurial ventures including agriculture. Obinna and Maduka (2017) assessed a sample of 120 non-farm rural entrepreneurs using multi-stage sampling through structured questionnaire to identify training needs. It was concluded that entrepreneurial training should include record keeping and ways to access capital.…”
Section: Overview Of Full Text Articlesmentioning
confidence: 99%